Understanding large temporal networks and spatial networks : exploration, pattern searching, visualization and network evolution - Batagelj, Vladimir; Doreian, Patrick; Ferligoj, Anuška; Kejžar, Nataša (Wiley Series in Computational and Quantitative Social Science, 2014)
This book explores social mechanisms that drive network change and link them to computationally sound models of changing structure to detect patterns. This text identifies the social processes generating these networks and how networks have evolved. Reviews: "this book is easy to read and entertaining, and much can be learned from it. Even if you know just about everything about large-scale and temporal networks, the book is a worthwhile read; you will learn a lot about SNA literature, patents, the US Supreme Court, and European soccer." (Social Networks) "a clear and accessible textbook, balancing symbolic maths, code, and visual explanations. The authors' enthusiasm for the subject matter makes it enjoyable to read" (JASSS)